Preparation method of crystalline PdCN and amorphous PdP core-shell nanoparticles

Through the chemical synthesis method of doping carbon, nitrogen and phosphorus of non-metal elements, crystalline PdCN@amorphous PdP core-shell nanoparticles were prepared, which solved the problem of difficult transformation of crystalline-amorphous heterostructure in platinum group metals, and achieved uniform size preparation of nanoparticles, simplified equipment and reagent treatment.

CN119683574AActive Publication Date: 2025-03-25JILIN UNIVERSITY

Patent Information

Application Number
CN202411886896.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-25
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The prior art is difficult to balance the transition between crystalline-amorphous heterostructures in platinum group metals, resulting in challenges in building crystalline @ amorphous core-shell heterostructures based on platinum group metals.

Method used

Crystalline PdCN@amorphous PdP core-shell nanoparticles were prepared by doping carbon, nitrogen and phosphorus through multi-step chemical synthesis. The method includes preparing cube Pd nanoparticles, converting them into cube PdCN nanoparticles, and mixing them with oleamine and trioctylphosphine by heating to form crystalline PdCN@amorphous PdP core-shell nanoparticles.

Benefits of technology

The uniformly sized crystalline PdCN@amorphous PdP core-shell nanoparticles were successfully prepared, which simplified the equipment requirements and reagent treatment, and the reagents used were available on the market, with a simple method.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683574A_ABST
    Figure CN119683574A_ABST
Patent Text Reader

Abstract

The invention is applicable to the technical field of synthesis and application of nano materials, and provides a preparation method of crystalline PdCN / amorphous PdP core-shell nanoparticles, which comprises the following steps: adding polyvinylpyrrolidone, L-ascorbic acid and potassium bromide into deionized water to form a mixed solution, preheating an oil bath pan, injecting a sodium chloropalladate solution, and stirring to obtain a mixed solution; transferring into an oil bath pan to react, centrifuging and cleaning to obtain cubic Pd nano-particles; dissolving in a dimethyl sulfoxide solution, transferring into a reaction kettle for reaction, centrifuging and cleaning to obtain cubic PdCN nanoparticles; and mixing the cubic PdCN nano-particles with an oleylamine solution, adding a trioctylphosphine solution, heating, centrifuging and cleaning to successfully obtain the crystalline PdCN and amorphous PdP core-shell nano-particles. Reagents used in the method can be purchased on the market and do not need to be further treated, the preparation method is simple, needed equipment is basic laboratory equipment, and expensive equipment and instruments are not needed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano material synthesis and application, and in particular relates to a method for preparing crystalline PdCN@amorphous PdP core-shell nanoparticles. Background Art

[0002] Since heterostructures were first proposed in wide-gap semiconductor emitter applications, they have attracted widespread attention in multiple energy fields due to their unique physical and chemical properties. In particular, heterostructured nanomaterials, due to the unique microstructure of the heterogeneous interfaces formed inside them, can fully absorb the advantages of individual components and abandon their inherent disadvantages, thereby producing a strong synergistic effect and significantly improving the performance of various electrochemical technologies, such as oxygen evolution reaction (OER), oxygen reduction reaction (ORR), carbon dioxide reduction reaction (CO2RR) lithium-ion batteries and sodium-ion batteries. At the same time, in the field of electrochemistry, crystalline materials based on platinum group metals are generally considered to be the most effective catalysts. Therefore, the synthesis of heterostructured materials based on platinum group metals has attracted much attention.

[0003] At present, most studies focus on heterostructures composed of two crystalline phases. However, in recent years, it has been reported that amorphous phase materials show extraordinary structural flexibility and better corrosion resistance in electrochemical catalysis compared with crystalline phases. This is mainly attributed to the following three aspects: first, the charge transfer in the heterojunction promotes electron redistribution, thereby adjusting the band structure of the components; second, the crystalline-amorphous hybrid structure can expose more vacancies on the surface, providing sufficient active sites for the catalytic reaction; third, the amorphous shell structure can effectively delay the dissolution or precipitation process of the reactants, thereby enhancing the stability of the catalyst. In addition, the core-shell structure has tunable catalytic performance, which can be controlled by changing the elemental composition and morphology, thereby optimizing the synergistic effect between different components and the combination of various properties. Therefore, the design of crystalline@amorphous core-shell heterojunction materials based on platinum group metals has become a hot topic in the field of electrochemistry. However, it is still challenging to construct such a heterostructure due to the difficulty in balancing the transition between crystalline-amorphous heterostructures in platinum group metals. In view of this, it is of great academic significance and application value to explore the synthesis of crystalline@amorphous core-shell heterojunction materials based on platinum group metals. To this end, the present invention proposes a method for preparing crystalline PdCN@amorphous PdP core-shell nanoparticles. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing crystalline PdCN@amorphous PdP core-shell nanoparticles, aiming to solve the problems raised in the above background technology.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A method for preparing crystalline PdCN@amorphous PdP core-shell nanoparticles comprises the following steps:

[0007] Step 1, preparing cubic Pd nanoparticles: adding polyvinyl pyrrolidone, L-ascorbic acid and potassium bromide into deionized water to form a mixed solution, preheating the oil bath, quickly injecting the sodium chloropalladate solution into the mixed solution, and then transferring the mixed solution to the oil bath. After the reaction is completed, the temperature is lowered to room temperature; the obtained solution is centrifuged and washed with deionized water, ethanol and acetone to obtain cubic Pd nanoparticles, which are dried for later use;

[0008] Step 2, preparing cubic PdCN nanoparticles: dissolving cubic Pd nanoparticles in a dimethyl sulfoxide solution, and transferring the solution to a reactor for reaction; centrifuging and washing the resulting solution with deionized water and ethanol to obtain cubic PdCN nanoparticles, and drying and storing the resulting cubic PdCN nanoparticles;

[0009] Step 3, preparing crystalline PdCN@amorphous PdP core-shell nanoparticles: mixing cubic PdCN nanoparticles with oleylamine solution, adding trioctylphosphine solution and heating; centrifuging and washing the obtained solution with ethanol and toluene to obtain crystalline PdCN@amorphous PdP core-shell nanoparticles.

[0010] Furthermore, the specific process of step 1 is as follows:

[0011] 1.05 g of polyvinyl pyrrolidone, 0.6 g of L-ascorbic acid and 6 g of potassium bromide were added to 80 mL of deionized water to form a mixed solution. The oil bath was preheated for 10 min until the temperature reached 85° C. 30 mL of 0.065 mol / L sodium chloropalladate solution was quickly injected into the mixed solution. The mixed solution was then transferred to an oil bath and reacted at 85° C. for 3 h, and the temperature was lowered to room temperature. The obtained solution was centrifuged and washed 2 to 3 times with deionized water, ethanol and acetone to obtain cubic Pd nanoparticles, which were dried for later use.

[0012] Furthermore, the specific process of step 2 is as follows:

[0013] 0.03 g of cubic Pd nanoparticles were weighed and dissolved in 60 mL of dimethyl sulfoxide solution, transferred to a reactor, and reacted at 180° C. for 2 h. The resulting solution was centrifuged and washed 2 to 3 times with deionized water and ethanol to obtain cubic PdCN nanoparticles, which were dried at 40° C. for storage.

[0014] Furthermore, the specific process of step 3 is as follows:

[0015] 21 mg of cubic PdCN nanoparticles were weighed and mixed with 77 mL of oleylamine solution, 7 mL of trioctylphosphine solution was added, and the mixture solution was heated at 200°C for 10 min; the resulting solution was centrifuged and washed with ethanol and toluene 2 to 3 times to obtain crystalline PdCN@amorphous PdP core-shell nanoparticles.

[0016] Furthermore, in step 1, during the first cleaning, acetone is used to separate the sample from the reaction solution, and the volume ratio of acetone to the reaction solution is 3:1; in the subsequent cleaning process, a mixture of deionized water, ethanol and acetone is used, and the volume ratio of deionized water, ethanol and acetone is 1:1:10.

[0017] Furthermore, in step 2, the number of cleaning times is 3 times, and the volume ratio of deionized water and ethanol used in the cleaning process is 1:5.

[0018] Furthermore, in step 3, the number of cleaning times is 3 times, and the volume ratio of ethanol and toluene used in the cleaning process is 1:1.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. The present invention successfully uses non-metallic elements to dope carbon, nitrogen and phosphorus for the first time to prepare crystalline PdCN@amorphous PdP core-shell nanoparticles with uniform size.

[0021] 2. The reagents used in the present invention can be purchased on the market and do not require further processing. The preparation method is simple and the required equipment is basic laboratory equipment, without the need for expensive equipment and instruments. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 These are the X-ray diffraction (XRD) patterns of cubic Pd nanoparticles, cubic PdCN nanoparticles and crystalline PdCN@amorphous PdP core-shell nanoparticles prepared in Example 1; wherein (a) is the XRD pattern of cubic Pd nanoparticles; (b) is the XRD pattern of cubic PdCN nanoparticles; and (c) is the XRD pattern of crystalline PdCN@amorphous PdP core-shell nanoparticles.

[0023] Figure 2 1 is a transmission electron microscope (TEM) image of the crystalline PdCN@amorphous PdP core-shell nanoparticles prepared in Example 1; wherein (a) is a TEM image at a 50 nm scale; and (b) is a TEM image at a 10 nm scale.

[0024] Figure 3 This is a scanning electron microscope image of the crystalline PdCN@amorphous PdP core-shell nanoparticles prepared in Example 1.

[0025] Figure 4These are the X-ray diffraction (XRD) patterns of cubic Pd nanoparticles, cubic PdCN nanoparticles and crystalline PdCN@amorphous PdP core-shell nanoparticles prepared in Example 2; wherein (a) is the XRD pattern of cubic Pd nanoparticles; (b) is the XRD pattern of cubic PdCN nanoparticles; and (c) is the XRD pattern of crystalline PdCN@amorphous PdP core-shell nanoparticles.

[0026] Figure 5 These are transmission electron microscope (TEM) images of the crystalline PdCN@amorphous PdP core-shell nanoparticles prepared in Example 2; (a) is a TEM image at a 50 nm scale; and (b) is a TEM image at a 10 nm scale.

[0027] Figure 6 This is a scanning electron microscope image of the crystalline PdCN@amorphous PdP core-shell nanoparticles prepared in Example 2. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and Examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Unless otherwise specified, the reagents used are all commercially available products and do not need to be further purified for use.

[0029] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.

[0030] Example 1: Synthesis of crystalline PdCN@amorphous PdP core-shell nanoparticles;

[0031] A method for synthesizing crystalline PdCN@amorphous PdP core-shell nanoparticles comprises the following steps:

[0032] 1) 1.05 g of polyvinyl pyrrolidone, 0.6 g of L-ascorbic acid and 6 g of potassium bromide were added to 80 mL of deionized water to form a mixed solution, and an oil bath was preheated for about 10 min until the temperature reached 85° C. 30 mL of a 0.065 mol / L sodium chloropalladate solution was quickly injected into the mixed solution, and the mixed solution was transferred to an oil bath, reacted at 85° C. for 3 h, and the temperature was lowered to room temperature; the obtained solution was centrifuged and washed with deionized water, ethanol and acetone to obtain cubic Pd nanoparticles, which were dried for later use.

[0033] Among them, the number of cleaning times is 3 times. In the first cleaning, acetone is used to separate the sample from the reaction liquid, and the volume ratio of acetone to the reaction liquid is 3:1; in the subsequent cleaning process, a mixture of deionized water, ethanol and acetone is used, and the volume ratio of deionized water, ethanol and acetone is 1:1:10.

[0034] 2) Weigh 0.03 g of cubic Pd nanoparticles and dissolve them in 60 mL of dimethyl sulfoxide solution, transfer them to a reactor, and react at 180° C. for 2 h; the resulting solution is centrifuged and washed three times with deionized water and ethanol to obtain cubic PdCN nanoparticles, which are then dried at 40° C. for storage.

[0035] The cleaning times were 3 times, and the volume ratio of deionized water and ethanol used in the cleaning process was 1:5.

[0036] 3) Weigh 21 mg of cubic PdCN nanoparticles and mix with 77 mL of oleylamine solution, add 7 mL of trioctylphosphine solution, and heat the mixture solution at 200° C. for 10 min; centrifuge and wash the resulting solution with ethanol and toluene three times to obtain crystalline PdCN@amorphous PdP core-shell nanoparticles.

[0037] The cleaning times were 3 times, and the volume ratio of ethanol and toluene used in the cleaning process was 1:1.

[0038] The XRD pattern of the sample prepared in this example is as follows Figure 1 As shown, transmission electron microscopy and element distribution photos are shown in Figure 2 , SEM and element distribution photos are shown in Figure 3 . The XRD spectrum shows that the product is crystalline PdCN@amorphous PdP core-shell nanoparticles. By comparing with the standard PdXRD spectrum, it is found that the characteristic peaks of the synthesized PdCN nanocrystals are shifted to a small angle compared with the standard Pd XRD card JCPDS-46-1043, indicating that C and N have successfully entered the Pd lattice to form PdCN nanocubes; after introducing P on the basis of PdCN, the XRD characteristic peak position of the obtained nanocrystals is almost the same as that of PdCN, indicating that the crystalline part is still PdCN. Transmission electron microscopy and element distribution photos and scanning electron microscopy and element distribution photos show that the synthesized nanocrystals are uniform in size, and the Pd, C, N, and P elements are evenly distributed in the nanoparticles, indicating that this example successfully synthesized crystalline PdCN@amorphous PdP core-shell nanoparticles.

[0039] Example 2: Synthesizing crystalline PdCN@amorphous PdP core-shell nanoparticles by changing the reaction temperature;

[0040] A method for synthesizing crystalline PdCN@amorphous PdP core-shell nanoparticles by changing the reaction temperature comprises the following steps:

[0041] 1) is the same as step 1) in Example 1.

[0042] 2) is the same as step 2) in Example 1.

[0043] 3) Weigh 21 mg of cubic PdCN nanoparticles and mix with 77 mL of oleylamine solution, add 7 mL of trioctylphosphine solution, and heat the mixture solution at 195° C. for 10 min; centrifuge and wash the resulting solution with ethanol and toluene three times to obtain crystalline PdCN@amorphous PdP core-shell nanoparticles.

[0044] The cleaning times were 3 times, and the volume ratio of ethanol and toluene used in the cleaning process was 1:1.

[0045] The XRD pattern of the sample prepared in this example is as follows Figure 4 As shown, transmission electron microscopy and element distribution photos are shown in Figure 5 , SEM and element distribution photos are shown in Figure 6 . The XRD spectrum shows that the product is crystalline PdCN@amorphous PdP core-shell nanoparticles. By comparing with the standard PdXRD spectrum, it is found that the characteristic peaks of the synthesized PdCN nanocrystals are shifted to a small angle compared with the standard Pd XRD card JCPDS-46-1043, indicating that C and N have successfully entered the Pd lattice to form PdCN nanocubes; after introducing P on the basis of PdCN, the XRD characteristic peak position of the obtained nanocrystals is almost the same as that of PdCN, indicating that the crystalline part is still PdCN. Transmission electron microscopy and element distribution photos and scanning electron microscopy and element distribution photos show that the synthesized nanocrystals are uniform in size, and the Pd, C, N, and P elements are evenly distributed in the nanoparticles. Compared with Example 1, the thickness of the amorphous shell synthesized in this example is thinner, indicating that this example successfully synthesized crystalline PdCN@amorphous PdP core-shell nanoparticles.

[0046] The above are only preferred embodiments of the present invention. It should be pointed out that, for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention. These should also be regarded as the protection scope of the present invention. These will not affect the effect of the implementation of the present invention and the practicality of the patent.

Claims

1. A method for preparing crystalline PdCN@amorphous PdP core-shell nanoparticles, characterized in that: The following steps are involved: Step 1, preparing cubic Pd nanoparticles: adding polyvinyl pyrrolidone, L-ascorbic acid and potassium bromide into deionized water to form a mixed solution, preheating the oil bath, quickly injecting the sodium chloropalladate solution into the mixed solution, and then transferring the mixed solution to the oil bath. After the reaction is completed, the temperature is lowered to room temperature; the obtained solution is centrifuged and washed with deionized water, ethanol and acetone to obtain cubic Pd nanoparticles, which are dried for later use; Step 2, preparing cubic PdCN nanoparticles: dissolving cubic Pd nanoparticles in a dimethyl sulfoxide solution, and transferring the solution to a reactor for reaction; centrifuging and washing the resulting solution with deionized water and ethanol to obtain cubic PdCN nanoparticles, and drying and storing the resulting cubic PdCN nanoparticles; Step 3, preparing crystalline PdCN@amorphous PdP core-shell nanoparticles: mixing cubic PdCN nanoparticles with oleylamine solution, adding trioctylphosphine solution and heating; The resulting solution was centrifuged and washed with ethanol and toluene to obtain crystalline PdCN@amorphous PdP core-shell nanoparticles.

2. The method for preparing crystalline PdCN@amorphous PdP core-shell nanoparticles according to claim 1, characterized in that: The specific process of step 1 is as follows: 1.05 g of polyvinyl pyrrolidone, 0.6 g of L-ascorbic acid and 6 g of potassium bromide were added to 80 mL of deionized water to form a mixed solution. The oil bath was preheated for 10 min until the temperature reached 85° C. 30 mL of 0.065 mol / L sodium chloropalladate solution was quickly injected into the mixed solution. The mixed solution was then transferred to an oil bath and reacted at 85° C. for 3 h, and the temperature was lowered to room temperature. The obtained solution was centrifuged and washed 2 to 3 times with deionized water, ethanol and acetone to obtain cubic Pd nanoparticles, which were dried for later use.

3. The method for preparing crystalline PdCN@amorphous PdP core-shell nanoparticles according to claim 1, characterized in that: The specific process of step 2 is as follows: 0.03 g of cubic Pd nanoparticles were weighed and dissolved in 60 mL of dimethyl sulfoxide solution, transferred to a reactor, and reacted at 180° C. for 2 h. The resulting solution was centrifuged and washed 2 to 3 times with deionized water and ethanol to obtain cubic PdCN nanoparticles, which were dried at 40° C. for storage.

4. The method for preparing crystalline PdCN@amorphous PdP core-shell nanoparticles according to claim 1, characterized in that: The specific process of step 3 is as follows: 21 mg of cubic PdCN nanoparticles were weighed and mixed with 77 mL of oleylamine solution, 7 mL of trioctylphosphine solution was added, and the mixture solution was heated at 200°C for 10 min; the resulting solution was centrifuged and washed with ethanol and toluene 2 to 3 times to obtain crystalline PdCN@amorphous PdP core-shell nanoparticles.

5. The method for preparing crystalline PdCN@amorphous PdP core-shell nanoparticles according to claim 2, characterized in that: In step 1, during the first cleaning, acetone is used to separate the sample from the reaction solution, and the volume ratio of acetone to the reaction solution is 3:1; in the subsequent cleaning process, a mixture of deionized water, ethanol and acetone is used, and the volume ratio of deionized water, ethanol and acetone is 1:1:

10.

6. The method for preparing crystalline PdCN@amorphous PdP core-shell nanoparticles according to claim 3, characterized in that: In step 2, the cleaning times are 3 times, and the volume ratio of deionized water and ethanol used in the cleaning process is 1:

5.

7. The method for preparing crystalline PdCN@amorphous PdP core-shell nanoparticles according to claim 4, characterized in that: In the step 3, the washing times are 3 times, and the volume ratio of ethanol and toluene used in the washing process is 1:1.

Citation Information

Patent Citations

  • Carbon nano tube loaded palladium @ vanadium-phosphorus-oxide compound core-shell nanoparticle and preparation method thereof

    CN105489906A

  • Palladium cubic nanocrystal with surface doped with phosphorus element as well as preparation method and application thereof

    CN109355677A

  • Iron-palladium / iron NANO composite magnet and manufacturing method thereof

    JP2015185602A

  • Metal nanoparticle-PCP complex and manufacturing method therefor

    US20140186253A1

  • Layered platinum on freestanding palladium nano-substrates for electrocatalytic applications and methods of making thereof

    US20160276674A1

Cited By

  • Method for preparing formate crystal by using core-shell microcapsule and product

    CN120247688A